PERAN THEORY OF PLANNED BEHAVIOR TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA PADA DISTRIK WANIA - Uvi Alfianzyah; Longginus Gelatan; Ignasius Narew (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to find out the factors that can affect the accountability of village fund management in Wania District. The method used in this study was associative. The data collection techniques performerd by researchers are observation techniques and questionnaires. The data analysis instrument used is multiple linear regression analysis with the help of SEM PLS. The result of this study show that attitude toward behavior has a significant effect on village fund management accountability in the Wania District, Subjective norm and self efficacy have no significant effect on village fund management accountability in Wania District.